Balancing Safety, Financial Performance, and Environmental Sustainability in Ghana’s Gold Mining Operations - William, Lokko George; Yang, Li; Pamela, Nguembi Ines; Linda, Abangbila (International Journal of Advanced Engineering Research and Science, 2023)
Gold mining that is rapidly expanding and has become an important means of revenue for an immense number of residents in geographic areas within which it is conducted. Nevertheless, despite this acknowledged possibility, gold extraction poses a variety of difficulties for those involved, with miner safety and health being particularly risky. Our study's objective is to investigate the balance between financial performance and safety in environmental sustainability in Ghana’s gold mining sector. By doing a case study, we use regression and descriptive statistics to examine the relationships between the variables to determine the tactics employed to strike a balance between safety, financial success, and environmental sustainability. These findings show that violations of occupational safety and health do occur in the gold mining sector in the research area. Consequently, the investigation recommends striking a balance between protection, monetary success, and sustainable development. A greater prevalence of protective clothing as well as routine incorporation of aerial photography into governmental evaluations of gold extraction operations are all attainable objectives for achieving requirements for workplace health and safety, boosting Ghana's economic output, and ensuring the longevity of the environment. we conclude that the findings of our study as gold mining industry in Ghana, which is rapidly expanding and widely practiced throughout Sub-Saharan Africa, is an important source of earnings for a large number of people in the regions where it is conducted. Nevertheless, regardless this acknowledged prospective, the extraction of gold presents a number of challenges to the individuals whose partake in it, with the well-being and security of laborers being especially important. The implementation of the latest cutting-edge approach should be made a policy they are as follows. The greatest environmental dangers are associated with conventional mining methods like open pit and underground mining. These practices should be banned and enforced. Mining waste reuse. Setting up other industries for the use of mining waste. This can help recycle mining waste and help make the environment safe and friendly